1996
DOI: 10.1038/380642a0
|View full text |Cite
|
Sign up to set email alerts
|

Control of cAMP-regulated enhancers by the viral transactivator Tax through CREB and the co-activator CBP

Abstract: The Tax protein of human T-lymphotropic virus (HTLV)-1 activates expression of the HTLV-1 long terminal repeat through a DNA element that resembles the cellular cyclic AMP-regulated enhancer (CRE). Tax contains a transcriptional activation domain, but its ability to activate gene expression depends on interactions with cellular CRE-binding proteins such as CREB. Whether Tax can activate the expression of cellular CRE-containing genes has been controversial. Here we show that Tax can activate both the HTLV-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
376
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(389 citation statements)
references
References 22 publications
12
376
1
Order By: Relevance
“…Given that binding to the co-activators is critical for Tax1 and Tax2-mediated transactivation (Kwok et al, 1996;Harrod et al, 1998;Kashanchi et al, 1998;Meertens et al, 2004b), we also undertook a series of experiments aiming at determining whether Tax3 could bind the CBP and p300 coactivators. Using the GFP, GFP-Tax1, GFP-Tax2 and GFP-Tax3 S proteins Characterization of the HTLV/STLV-3 Tax protein SA Chevalier et al expressed from 293T-transfected cells, we performed a series of co-immunoprecipitations as previously described (Meertens et al, 2004b).…”
Section: Resultsmentioning
confidence: 99%
“…Given that binding to the co-activators is critical for Tax1 and Tax2-mediated transactivation (Kwok et al, 1996;Harrod et al, 1998;Kashanchi et al, 1998;Meertens et al, 2004b), we also undertook a series of experiments aiming at determining whether Tax3 could bind the CBP and p300 coactivators. Using the GFP, GFP-Tax1, GFP-Tax2 and GFP-Tax3 S proteins Characterization of the HTLV/STLV-3 Tax protein SA Chevalier et al expressed from 293T-transfected cells, we performed a series of co-immunoprecipitations as previously described (Meertens et al, 2004b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that c-Myb and Tax proteins interact with the same region of CBP in a signal-independent manner, amino acid residues 461 ± 661 and 451 ± 682, respectively (Dai et al, 1996;Oelgeschlager et al, 1996;Kwok et al, 1996). Because c-Myb can transactivate its own promoter in Jurkat T-cells (Figure 1c), we tested whether competition between c-Myb and Tax for the recruitment of CBP or p300 could explain Tax-mediated repression of the c-Myb promoter.…”
Section: Repression Of the C-myb Promoter By The Tax Protein Through mentioning
confidence: 97%
“…Since Tax is reported to bind to CBP/p300 (Bex et al, 1998;Kwok et al, 1996), we examined the possibility that Tax binding to CBP/p300 a ects its function in these two systems.…”
Section: Inhibition Of Cbp/p300-directed Transcription By Taxmentioning
confidence: 99%
“…Furthermore, Tax interacts with a transcriptional coactivator, CBP, which binds to the phosphorylated form of CREB (Chrivia et al, 1993). Through these binding capacities, Tax functions as a linker between CREB and CBP in a phosphorylation-independent manner on the viral enhancer, the 21-bp element (Giebler et al, 1997;Harrod et al, 1998;Kwok et al, 1996;Lenzmeier et al, 1998).…”
Section: Introductionmentioning
confidence: 99%